Evaluation of Single Vehicle Noise Emission in Different Speed Conditions. (September 2020) - Graziuso, G; Mancini, S; Quartieri, J; Guarnaccia, C
Abstract: Because of the increase of vehicles number, the evaluation and monitoring of road traffic noise assume a significant role for decreasing risks for human health and managing environmental pollution in urban areas. Noise measurements cannot be performed everywhere, or even in a large number of sites, because of high costs and time consumption. For this reasons, Road Traffic Noise predictive Models (RTNMs) can be implemented to estimate the noise levels, knowing certain parameters needed as input. This paper describes the comparison of the results, in terms of sound power level emitted by a single vehicle, obtained with the application of some Emission Models (EMs) to different simulations of driving conditions. After a preliminary comparison between the models, the evaluation of two indicators, namely the average and total source power level, will be discussed in relation to different conditions of the vehicle kinematics.